Syphilis Notification Systems in Korea over the Last 20 Years - Yumi Seo; Gilho Lee (Urogenital Tract Infection)
Purpose The syphilis notification system has been revised three times in Korea during the last 20 years. Accordingly, we evaluated the performance of the three systems by analyzing data from the Korea Disease Control and Prevention Agency (KDCA). Materials and Methods We analyzed trends of stage 1, 2, and congenital syphilis cases reported in the KDCA from 2001 to 2010 in the 1st sentinel (S1), from 2011 to 2019 in the 1st universal (U1), and 2020 in the 2nd sentinel (S2) notification system. Results A total of 21,820 syphilis cases were reported, 9,177 cases in S1, 12,321 in U1, and 322 in S2, respectively. The reported cases can be presented in the form of four expanding waves across the time period. Although the most commonly reported age group with infection was 20-29 years in all three reporting systems, the pattern of infections was different; the number of older patients was relatively high in the S1 group while the number of syphilis cases declined sharply in the older than 20-29 old age group in the U1 and S2 systems. Also, there was a sex-based difference in the three groups; the data from S1 were female-dominant but the data in U1 and S2 were male-dominant. Conclusions Our results showed that the universal notification system (U1) is superior in both the quantity and quality of data to the previous sentinel system (S1). The results from the new system, S2, are similar to those from U1.